Revitalization of Batu Songgan Traditional Village in Sustainable Development - Mimin Sundari Nasution; Risky Arya Putri (Iapa Proceedings Conference, 2019)
Customary villages are traditional autonomous institutions, traditional cultural communities, indigenous law communities, and local identities. Batu Songgan Village is one of the traditional villages which is included in the Bukit Rimbang Wildlife Reserve in Bukit Baling in Riau. Local cultural values that are beginning to be neglected in life today are an important issue. Revitalization of the village or the traditional village is a process or way reactivate potentials in order to conserve the indigenous villages. An important value possessed by indigenous peoples in their relationship with the exploration and exploitation of nature . But the reality is a decline in the functions of traditional villages in maintaining environmental sustainability, resulting in ecosystem damage that causes a number of problems, such as flooding, siltation of rivers due to precipitation of sludge, decreasing productivity of crops, fisheries and so on. local communities, the effort to maintain ecosystems in an integrated manner is a strategic effort in the context of sustainable the traditional Village management. Based on this important issue, this study aims to see how the revitalization of the traditional Batu songgan village in sustainable development. Analysis of this study using library research methods (library research). The revitalization research of Batu Songgan traditional village has been carried out with 3 approaches namely physical intervention, economic rehabilitation and social / institutional revitalization. Based on the results of the study, it is known that physical intervention is still weak or not good, while economic rehabilitation and social / institutional revitalization are good enough but still need significant improvement.